2005
DOI: 10.1021/jf0517804
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Compounds in Chilled Cod (Gadus morhua) Fillets by Gas Chromatography and Detection of Quality Indicators by an Electronic Nose

Abstract: Volatile compounds in cod fillets packed in Styrofoam boxes were analyzed during chilled storage (0.5 degrees C) by gas chromatography (GC)-mass spectrometry and GC-olfactometry to screen potential quality indicators present in concentrations high enough for detection by an electronic nose. Photobacterium phosphoreum dominated the spoilage bacteria on day 12 when the fillets were rejected by sensory analysis. Ketones, mainly 3-hydroxy-2-butanone, were detected in the highest level (33%) at sensory rejection, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 36 publications
9
92
0
Order By: Relevance
“…Otherwise, differences in new batches caused by, for example, different fishing grounds, the fishing season, the fat content in the flesh, or physical damages due to rough handling and bruising will not be taken into account. 98,99 A very good study about the potential of electronic noses in this field was presented by Olafsdottir et al 100 Using a fundamental approach, the chemical reason for the sensor response of an electronic nose consisting of four electrochemical gas sensors was identified. The experimental setup used included microbial analysis, determination of TVBN, pH measurements, GC/MS measurements, and GC-O measurements.…”
Section: Food and Beveragementioning
confidence: 99%
“…Otherwise, differences in new batches caused by, for example, different fishing grounds, the fishing season, the fat content in the flesh, or physical damages due to rough handling and bruising will not be taken into account. 98,99 A very good study about the potential of electronic noses in this field was presented by Olafsdottir et al 100 Using a fundamental approach, the chemical reason for the sensor response of an electronic nose consisting of four electrochemical gas sensors was identified. The experimental setup used included microbial analysis, determination of TVBN, pH measurements, GC/MS measurements, and GC-O measurements.…”
Section: Food and Beveragementioning
confidence: 99%
“…Trimethylamine is a thermal decomposition product of choline, betaine, methionine, or most likely, trimethylamine oxide during cooking [18]. It has been reported as an important odorant in cooked E. sinensis [11], lobster [18], and cod [19] in high concentrations. Due to its high content and intense aroma in this study, trimethylamine could be a net contributor to the aroma of three parts-claw meat, leg meat, and the gonad-of E. sinensis.…”
Section: Discussionmentioning
confidence: 99%
“…1-Penten-3-ol was reported to be the product of the action of lipoxygenases on ω-3 PUFA (German et al, 1992;Hu and Pan, 2000). 1-Penten-3-ol could also be caused by Pseudomonas species and can contribute to the stale and putrid off odors in fish (Miller et al, 1973;Olafsdottir et al, 2005). Nakamura et al (1980) also found that 1-penten-3-ol may be produced by microbial spoilage.…”
Section: Tvb-n and Sensory Evaluationmentioning
confidence: 99%
“…Heptanal was described to have an earthy and boiled-potato like smell and may cause the fishy odor in cold stored cod (Karahadian and Lindsay, 1989;Olafsdottir et al, 2005;Maqsood and Benjakul, 2011). Heptanal can be used as a reliable indicator of flavor deterioration for fish products, while hexanal is related with the rancidity in meats (Augustin et al, 2006;Ross and Smith, 2006).…”
Section: Tvb-n and Sensory Evaluationmentioning
confidence: 99%
See 1 more Smart Citation